Self‐regenerating black medic cover crop provides agronomic benefits at low nitrogen. (17th August 2022) - May, William E.; McConachie, R.; Entz, Martin
Abstract: A black medic ( Medicago lupulina L.) cover crop is able to regenerate from seed annually and produce biomass at the end of each growing season, but its long‐term effectiveness on crop productivity, water use efficiency (WUE), and soil nutrient status within a no‐till cropping system is unclear. A field experiment was established in 2003 in Saskatchewan in a 3‐yr crop rotation [flax ( Linum usitatissimum L.)–oat ( Avena sativa L.)–wheat ( Triticum aestivum L.)]. Treatments included cover crop (black medic or no medic), and N fertilizer (20, 60, and 100% of recommended N) arranged in a split‐split plot design. Over 10 yr, medic aboveground fall biomass averaged 625 kg ha –1 (range 0–1, 868 kg ha –1 ) and was greatest at the lowest N rate, 879 kg ha –1 . Medic increased grain yield at 20% N fertilizer; no effect was observed at higher N rates. Medic increased tiller density and kernel weight at 20% N, indicating that medic positively influenced the crop throughout the entire life cycle. Medic presence did not affect grain N or P status. Medic did not affect level of available soil N in fall but consistently increased level of soil available P. This extended to the 30–60 cm soil depth in the 100% vs. lower N rates, suggesting medic roots may have influenced P cycling. In oat stubble, medic increased spring soil water and WUE. In conclusion, black medic improved crop productivity at the low N rate but improved available soil P at all N rates, warranting further research. Core Ideas: This is the first North American study to evaluate long‐term effects of medic in a no‐till system. Medic had its greatest effect at 20% vs. 60 and 100% recommended fertilizer N. At the 20% N rate, medic increased grain yield (14%), grain N and P, and WUE. Medic presence increased soil P concentration at the 100% N rate and at deeper soil depths.